2017 39th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2017
DOI: 10.1109/embc.2017.8037468
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive diagnosis of non-alcoholic fatty liver disease (NAFLD) using ultrasound image echogenicity

Abstract: This paper introduces a non-invasive, quantitative technique to diagnose the progression of non-alcoholic fatty liver disease (NAFLD). The method is predicated on two fundamental principles: 1) the speed of sound in a fatty liver is lower than that in a healthy liver and 2) the quality of an ultrasound image is maximized when the beamformer’s speed of sound matches the true speed of sound in the tissue being examined. The proposed method uses the echogenicity of an ultrasound image as a quantitative measure to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 22 publications
(25 reference statements)
0
7
0
1
Order By: Relevance
“…Liver biopsy is the current gold-standard for NAFLD diagnosis, but this invasive procedure has high degrees of variability and sampling error in addition to carrying associated risks and costs [5,6]. Liver biopsies have proved to be subjective with up to 50% of pathologist reads resulting in disagreement [7].…”
Section: Introductionmentioning
confidence: 99%
“…Liver biopsy is the current gold-standard for NAFLD diagnosis, but this invasive procedure has high degrees of variability and sampling error in addition to carrying associated risks and costs [5,6]. Liver biopsies have proved to be subjective with up to 50% of pathologist reads resulting in disagreement [7].…”
Section: Introductionmentioning
confidence: 99%
“…Crosstalk between the liver and the immune system has the potential for integrating the sensing of nutrients and pathogens 57 , and could begin to explain the effects of diet and gut microbiota on T1D development. Recent advances in non-invasive imaging methods such as magnetic resonance spectroscopy and ultrasound elastography may enable testing of this hypothesis in children at-risk of developing T1D 58,59 .…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have also shown that longitudinal wave sound speed has similar diagnostic ability to shear wave imaging [11], [31], [32], [33], [34], [35]. Some of these results taken on breast tissue are presented in Table II (from [33]).…”
Section: Clinical Motivationmentioning
confidence: 92%